The experience of solving problems of monothorods (on the example of Kazakhstan and Germany) - Mukhambetkaliyeva Г.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
The article deals with the experience of solving urgent problems of development mono-cities (on the example of Kazakhstan and Germany). Analyzed the possibility of applying German experience in Kazakhstani conditions based on the method of comparative analysis implementation support policy of single-industry towns in Germany. The main problems of realization policy of single cities in Kazakhstan and Germany are allocated, comparison of monocities of two countries in terms of their spatial localization, socio-economic situation. The main directions of solving the problems of single-industry towns are determined, the timely solution of which is seen in the definition of promising directions and mechanisms of state support of single-industry towns, creation of partnership between different sectors of the economy, proposed some mechanisms that provide a targeted choice of solutions. The results obtained will be in demand in the process scientific-analytical substantiation of decisions in the sphere of state support of single-industry towns.